Spectral Analysis of Forest Fire Noise for Early Detection using Wireless Sensor Networks; Control and Communications (SIBCON) - Khamukhin A. A. Aleksandr Anatolievich (Sensors and Systems of the Internet of Things, 2016)
Title screen